Relative incidence of cucurbit viruses and relationship with bio-meteorological variables - Pozzi, Elizabeth Alicia; Bruno, Cecilia Inés; Luciani, Cecilia; Celli, Marcos Giovani; Conci, Vilma Cecilia; Perotto, Maria Cecilia (Springer, 2020)
Environmental heterogeneity can shape the plant-virus relationship, furthering the appearance of new diseases in crops, or altering disease incidence and severity. In this work, we studied the virus association with environmental heterogeneity taking into account bio-meteorological variables and virus distribution. In Argentina, three potyviruses, Watermelon mosaic virus (WMV), Zucchini yellow mosaic virus (ZYMV), and Papaya ringspot virus (PRSV), and a cucumovirus, Cucumber mosaic virus (CMV), are the most common viruses infecting cucurbits. We identified the bio-meteorological variables that had the greatest impact on disease incidence. All the crops were infected with more than one virus in all the studied environments. Molecular and serological analyses showed the highest relative incidence for WMV (46%), the lowest for CMV (9%), and intermediate values for PRSV and ZYMV (20% and 24%, respectively). Infected plants had a random distribution. Viruses and bio-meteorological variables were highly correlated, with high support (Pearson’s r = 0.96, P < 0.001). Temperature variables were negatively correlated with the three potyviruses. CMV was positively correlated with temperature. Relative humidity was positively correlated with potyviruses, but was not correlated with CMV. Our research field data and analyses may help to predict the outbreak of viral diseases in cucurbits crops.